Correlation of Activeness in the Youth Association of Al-Muhajirin Mosque with the Level of Juvenile Delinquency in Talang Kelapa District, Banyuasin Regency - Nur Hisnah Vania; Neni Noviza; Hartika Utami Fitri (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Adolescents are a developmental phase that is vulnerable to deviant behavior, so coaching is needed through religious activities such as the Mosque Youth Association (IRMAS), therefore this study aims to find out the level of youth activity in the Al-Muhajirin Mosque Youth Association, the level of juvenile delinquency, and the correlation between the two in Talang Kelapa District, Banyuasin Regency by using a quantitative approach through the distribution of questionnaires to 44 member respondents IRMAS Al-Muhajirin and analyzed using the Spearman Rank correlation test, the results showed that the activity rate of adolescents was in the medium category of 68.2% and the level of juvenile delinquency was in the medium category of 70.5%, and a correlation coefficient value of -0.609 with a significance of < 0.05 which indicates a strong and negative relationship, so that the higher the activity of adolescents in IRMAS activities, the lower the delinquency rate adolescents, thus being active in the Mosque Youth Association plays an important role in forming positive behavior and minimizing juvenile delinquency.